THE ROLE OF LABORATORY EXPERIMENTS IN VOLCANOLOGY - Mader H.M.; Manga M.; Koyaguchi T. (My University, 2004)
Experiment is central to scienti¢c methodology. Within science in general, experiments are used for four primary purposes, i.e. as a tool to explore novel phenomena and to provide systematic observations of processes, to determine the values of key parameters, to test hypotheses and theoretical models, and to validate computational models, which themselves can be considered as numerical experiments. The study of volcanic eruptions and magmatic processes is becoming increasingly systematic, quantitative and rigorous.